Estimación de los contenidos de carbono del ecosistema páramo del parque nacional Podocarpus-Ecuador - Moreno Romero, Gabriela Ivanova (2017)
The paramo has great potential of carbon storage, due to the low rates of mineralization and high recycling of nutrients, as a consequence of its low temperatures. The present research was carried out with the purpose of quantifying the total carbon (soil, necromass and soil) contents of the PNP paramo ecosystem and its spatial distribution, for which 80 temporary plots of 1m2 were installed, where the content was quantified of carbon in biomass and necromass by the destructive method. To determine the carbon content in the soil, two samples of soil were taken, one disturbed to determine the carbon content in the soil by the modified method of Walkley and Black (1947) and the second sample in a Kopecky cylinder to determine the density Apparent and hydrophysical constants of the soil. To determine its spatial distribution, the IDW interpolation method was used in the ArcGis 10.2 software. As a result the average carbon content was 163.11 ha -1, where the soil contributed 90% of carbon with one with a high positive correlation (r = 0.99) and the vegetation did not significantly influence In its content. Spatially the highest total carbon contents were found in the lake systems of the "Lagunas del Compadre", and the lowest contained in the north and south ends of the paramo ecosystem. The external variables that influenced its carbon content were: altitude (rs = 0.45), temperature (rs = -0.47), soil Hd% to CC (1/3 atm) (rs = 0.64 ) And the soil Hd% at Sat (0 atm) (rs = 0.79). Keywords: ecosystem paramo, soil carbon, carbon storage, necromass, biomass.